On the role of stress waves in dynamic rupture of cylindrical tubes. Issue 12 (27th April 2017) - Mirzaei, M.; Tavakoli, S.; Najafi, M.
Abstract: A systematic experimental/computational study was performed to investigate the role of stress waves in ductile fracture of cylindrical tubes. The stress waves were created by high‐speed moving load, which was produced by detonation of explosive cord inside two intact and two pre‐flawed steel tubes. Several distinct phenomena like cyclic crack growths in Modes I and III, crack flap bulging and crack curving/branching were observed and simulated by finite element (FE) method. The FE models were composed of 3D brick elements equipped with interface cohesive elements. The analysis results showed that the crack growths in Modes I and III were governed by the detonation‐induced stress waves. The crack speeds were obtained based on the increments of cyclic crack growth and the time period of the stress waves. The estimated crack speed range was 63–230 m s −1 for the axial growth, whereas the average speed for growth in Mode III was 100 m s −1 .